From coexistence to competitive exclusion: can overfishing change the outcome of competition in skates (Chondrichthyes, Rajidae)? - Ruocco, Natalia Lorena (2012)
Competition for food could be a major force driving changes in the community structure of skates (Rajidae) subjected to fishing exploitation. Under this hypothesis, small skates are released from competition with larger skates after fishing has depleted the larger species. Here, we compare the abundance patterns of two sympatric skates with similar niches but different life histories, Bathyraja albomaculata (larger and slow-reproducing) and Bathyraja macloviana (smaller and faster-reproducing), before (1971, 1978) and after (1998-2004) a 108% increase in industrial bottom trawling on the southeastern South American shelf in order to test the prediction that B. macloviana should competitively exclude B. albomaculata after the increase in fishing mortality. In 1971 and 1978, there was no relationship between the abundance of both species, indicating that they coexisted over large scales. In 1998-2004, the relationship between the abundances of these skates was bell-shaped, indicating that both species increased in abundance at low densities until peaking, after which B. albomaculata decreased when B. macloviana became more abundant, consistent with resource competition. We tested whether food may be a potential limiting resource by comparing the diet of both species. The two species consumed mostly polychaetes, differing only in the consumption of polychaetes from the family Nephthyidae, which was much higher for B. macloviana. Bathyraja macloviana could replaceBathyraja albomaculata (larger and slow-reproducing) and Bathyraja macloviana (smaller and faster-reproducing), before (1971, 1978) and after (1998-2004) a 108% increase in industrial bottom trawling on the southeastern South American shelf in order to test the prediction that B. macloviana should competitively exclude B. albomaculata after the increase in fishing mortality. In 1971 and 1978, there was no relationship between the abundance of both species, indicating that they coexisted over large scales. In 1998-2004, the relationship between the abundances of these skates was bell-shaped, indicating that both species increased in abundance at low densities until peaking, after which B. albomaculata decreased when B. macloviana became more abundant, consistent with resource competition. We tested whether food may be a potential limiting resource by comparing the diet of both species. The two species consumed mostly polychaetes, differing only in the consumption of polychaetes from the family Nephthyidae, which was much higher for B. macloviana. Bathyraja macloviana could replaceBathyraja macloviana (smaller and faster-reproducing), before (1971, 1978) and after (1998-2004) a 108% increase in industrial bottom trawling on the southeastern South American shelf in order to test the prediction that B. macloviana should competitively exclude B. albomaculata after the increase in fishing mortality. In 1971 and 1978, there was no relationship between the abundance of both species, indicating that they coexisted over large scales. In 1998-2004, the relationship between the abundances of these skates was bell-shaped, indicating that both species increased in abundance at low densities until peaking, after which B. albomaculata decreased when B. macloviana became more abundant, consistent with resource competition. We tested whether food may be a potential limiting resource by comparing the diet of both species. The two species consumed mostly polychaetes, differing only in the consumption of polychaetes from the family Nephthyidae, which was much higher for B. macloviana. Bathyraja macloviana could replaceB. macloviana should competitively exclude B. albomaculata after the increase in fishing mortality. In 1971 and 1978, there was no relationship between the abundance of both species, indicating that they coexisted over large scales. In 1998-2004, the relationship between the abundances of these skates was bell-shaped, indicating that both species increased in abundance at low densities until peaking, after which B. albomaculata decreased when B. macloviana became more abundant, consistent with resource competition. We tested whether food may be a potential limiting resource by comparing the diet of both species. The two species consumed mostly polychaetes, differing only in the consumption of polychaetes from the family Nephthyidae, which was much higher for B. macloviana. Bathyraja macloviana could replaceB. albomaculata decreased when B. macloviana became more abundant, consistent with resource competition. We tested whether food may be a potential limiting resource by comparing the diet of both species. The two species consumed mostly polychaetes, differing only in the consumption of polychaetes from the family Nephthyidae, which was much higher for B. macloviana. Bathyraja macloviana could replaceB. macloviana. Bathyraja macloviana could replace B. albomaculata at high densities when food resources may become scarce. These results support the hypothesis that competition release is an important factor explaining the changes in skate communities in overexploited areas.at high densities when food resources may become scarce. These results support the hypothesis that competition release is an important factor explaining the changes in skate communities in overexploited areas.